STRESS-REGULATED PROTOCOLS FOR FAST CHARGING IN LITHIUM-ION BATTERIES (MT) - YIN XinYu; GAO ErYue; ZHAO YanFei (Jixie qiangdu)
Inspired by the intrinsic degradation mechanism within the battery during fast charging, a stress-regulation（SR） fast charging method for lithium-ion battery is proposed by considering the diffusion-induced stress in the positive active particles. In the SR protocol, the diffusion-induced stress within the active particle reaches the critical value rapidly in the very early stage of the charging and maintains that value throughout the whole charging process. Furthermore, the constant-current stress-regulation（CCSR） protocol which contains an initial constant current stage and a following stress-regulated stage is proposed to resolve the issue of the theoretically infinite current at the beginning of the SR protocol. Compared with the constant current charging method, the boost charging method and the exponential current charging method, the proposed protocols provide an effective fast charging scheme for balancing the charging speed, the peak stress and the available capacity.